Vida e Doutrina de Santa Teresa de Jesus e de S. Joao da Cruz - Jose, Jaime de S. (Eidcoes dos Carmelitas Descalcos, 1947)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 6.Yellowing 變黃; Fair